Implementasi Sistem Pendekatan Manajemen Pengajaran dan Pembelajaran - Amiruddin Amiruddin; Tiwi Wulandari; Anisah Anisah; Muhammad Irvan Marsya; Ansari Fahmi (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Framework is a group of parts or components that collaborate with each other to achieve a goal. In planning the educational and learning framework and the instructive and preparatory strategies made in the modern and military fields. The idea is reason to recognize the target of the framework. The reason is that frameworks can be regular and human. Training is more centered around character styling and improvement. While preparing emphasizes the development of training abilities carried out in a school climate, while the use of preparation is largely based on a modern climate. In this way, the standards of learning are guidelines for educators in implementing successful learning conditions. There are two attributes of the show framework approach, in particular the teaching and developing framework and experience approach to make it simple for students to learn. Keywords: Implementasi, Sistem, Manajemen, Pengajaran, Pembelajaran.